Performance investigation of a novel near‐isothermal compressed air energy storage system with stable power output. (9th August 2020) - Zhao, Pan; Lai, Yongquan; Xu, Wenpan; Zhang, Shiqiang; Wang, Peizi; Wang, Jiangfeng
Summary: As one of the grid‐scale energy storage technologies, compressed air energy storage (CAES) is promising to facilitate the permeability of renewable energies. By integrating CAES into renewable sources, the fluctuation and intermittence of renewable energies could be effectively restrained. Among various CAES system configurations, isothermal CAES (I‐CAES) is considered as a most competitive technology with expected high efficiency. However, most of the existing I‐CAES systems have trouble in keeping a stable power output. To address this issue, a novel near‐isothermal CAES system is proposed in this article to acquire a near stable power output. Imitating the concept of hydraulic accumulator, a two pressure vessels structure is employed to maintain the gas pressure stable during discharging. Besides, the turbine power output can be controlled by adjusting the liquid flow rate of the Pelton turbine under this near constant pressure condition. Based on the system transient model and economic model, the system components transient behavior, parametric analysis, off‐design performance analysis and economic evaluation issues are also conducted. Results show that system round trip efficiency (RTE) with 61.42% and energy density (ED) with 0.2015 kWh/m 3 can be achieved under design condition. In the discharge process, the gas pressure in vessel varies in a small range, from 68 to 72 bar, which is relatively stable. The power output from Pelton turbine can be maintained around 1 kW. Meanwhile, the initial pressure, the pipe diameter, and the spraying flow rates of circulating pumps have significant effects on system RTE and ED. Furthermore, the Pelton turbine power output level can be adjusted by adding jets number, and the higher storage pressure can make the power output unsteady. Abstract : A novel near‐isothermal compressed air energy storage (CAES) system with stable power output is proposed. The transient model is conducted to analyze the thermodynamic performance. The effect of several key parameters on the system performance is studied. The system performance under off‐design conditions is predicted.